A H2O2 self-sufficient nanoplatform with domino effects for thermal-responsive enhanced chemodynamic therapy. Issue 7 (16th January 2020) - Zhang, Shichao; Cao, Changyu; Lv, Xinyi; Dai, Hanming; Zhong, Zhihao; Liang, Chen; Wang, Wenjun; Huang, Wei; Song, Xuejiao; Dong, Xiaochen
Abstract : Phase change material based H2 O2 self-supply nanoparticles for enhanced thermal responsive chemodynamic tumor therapy. Abstract : Chemodynamic therapy (CDT), employing Fenton or Fenton-like catalysts to convert hydrogen peroxide (H2 O2 ) into toxic hydroxyl radicals (˙OH) to kill cancer cells, holds high promise in tumor therapy due to its high selectivity. However, the anticancer efficacy is unsatisfactory owing to the limited concentration of endogenous H2 O2 . Herein, thermal responsive nanoparticles with H2 O2 self-sufficiency are fabricated by utilizing organic phase change materials (PCMs) to encapsulate iron–gallic acid nanoparticles (Fe–GA) and ultra-small CaO2 . PCMs, acting as the gatekeeper, could be melted down by the hyperthermia effect of Fe–GA under laser irradiation with a burst release of Fe–GA and CaO2 . The acidic tumor microenvironment would further trigger CaO2 to generate a large amount of H2 O2 and Ca 2+ . The self-supplied H2 O2 would be converted into ˙OH by participating in the Fenton reaction with Fe–GA. Meanwhile, in situ generation of Ca 2+ could cause mitochondrial damage and lead to apoptosis of tumor cells. With efficient tumor accumulation illustrated in in vivo photoacoustic imaging, Fe–GA/CaO2 @PCM demonstrated a superior in vivo tumor-suppressive effect without inducing systemic toxicity. The study presents a unique domino effect approach of PCM based nanoparticles with thermal responsiveness, H2 O2 self-supply, and greatly enhanced CDT effects, showing bright prospects for highly efficient tumor treatment.